ETIOLOGICAL PROFILE OF NEONATAL SEIZURES WITH SPECIAL REFERENCE TO BIOCHEMICAL ABNORMALITIES - Dhanjal, Gurdeep Singh; Singh, Vikramjot; Singh, Gurnoor (Journal of Biomedical and Pharmaceutical Research, 2019)
Introduction: Neonatal seizure are the most frequent manifestation of neurological dysfunction in a neonate. Detection of seizure and its etiology is important for guiding therapy. In the presence of biochemical abnormalities, it is difficult to control seizures and there is a risk of further brain damage. Early recognition and treatment of biochemical abnormalities are essential for optimal management and satisfactory long term outcome. The aim was to determine the etiology of neonatal seizures and to study the biochemical abnormalities. Material and Methods: The present study included 70 inborn neonates presenting with seizures admitted to the neonatal unit in MMIMSR, Mullana, Ambala, Haryana, India over a period of one and a half years. A detailed history was taken and clinical examination of the neonate was done. Etiological causes and various biochemical parameters were evaluated. Results: Neonatal seizures occurred more commonly in males. The most common cause of neonatal seizures was birth asphyxia seen in 26 (37.1%) neonates followed by sepsis in 24 (34.3%) neonates. The Primary Biochemical abnormalities were seen in 12 (17.1%) neonates with seizures. Among these neonates, hypoglycemia was most commonly seen in 4 (33.3%) neonates followed by hypocalcemia seen in 3 (25%) neonates. Conclusion: Biochemical abnormalities are common in neonatal seizures and often go unrecognized. These abnormalities may significantly contribute to seizure activity and hence a biochemical workup is necessary for all cases of neonatal seizures.